2015
DOI: 10.1890/14-0662.1
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of human impact: size distributions and spatial organization of wetlands in the Prairie Pothole landscape

Abstract: More than 50% of global wetland area has been lost over the last 200 years, resulting in losses of habitat and species diversity as well as decreased hydrologic and biogeochemical functionality. Recognition of the magnitude of wetland loss as well as the wide variety of ecosystem services provided by wetlands has in recent decades led to an increased focus on wetland restoration. Restoration activities, however, often proceed in an ad hoc manner, with a focus on maximizing the total restored area rather than o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
159
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 138 publications
(160 citation statements)
references
References 53 publications
1
159
0
Order By: Relevance
“…In a previous study, Van Meter and Basu (2015) quantified the historical and current size-frequency functions of depressional wetlands in the southernmost lobe of the PPR (Iowa), and found that, in addition to an overall loss of wetlands across the size classes, there has been a preferential loss of smaller wetlands in upland locations and may allude to a preferential loss of biogeochemical processes in the landscape Indeed, small, geographically isolated wetlands (GIWs) are considered to be at particular risk of drainage due to both a lack of legislative protections and general patterns of land development, i.e. the smallest wetlands are the easiest to drain, and their importance in landscape functionality (whether hydrologically, biogeochemically or ecologically) is easily underestimated [Van Meter and Basu, 2015]. GIWs are defined as wetland systems that do not have an apparent surface connection to a nearby water body (such as a river or lake) and thus are completely surrounded by uplands [Leibowitz, 2015]; however, it should be noted that many GIWs are connected through subsurface pathways or are seasonally connected for a portion of the year and form wetland complexes and thus are not 'visibly' connected or deemed to be useful [Leibowitz and Vining, 2003;Johnson et al, 2010].…”
Section: Small Wetlands As Biogeochemical Hotspots In Landscapesmentioning
confidence: 90%
See 4 more Smart Citations
“…In a previous study, Van Meter and Basu (2015) quantified the historical and current size-frequency functions of depressional wetlands in the southernmost lobe of the PPR (Iowa), and found that, in addition to an overall loss of wetlands across the size classes, there has been a preferential loss of smaller wetlands in upland locations and may allude to a preferential loss of biogeochemical processes in the landscape Indeed, small, geographically isolated wetlands (GIWs) are considered to be at particular risk of drainage due to both a lack of legislative protections and general patterns of land development, i.e. the smallest wetlands are the easiest to drain, and their importance in landscape functionality (whether hydrologically, biogeochemically or ecologically) is easily underestimated [Van Meter and Basu, 2015]. GIWs are defined as wetland systems that do not have an apparent surface connection to a nearby water body (such as a river or lake) and thus are completely surrounded by uplands [Leibowitz, 2015]; however, it should be noted that many GIWs are connected through subsurface pathways or are seasonally connected for a portion of the year and form wetland complexes and thus are not 'visibly' connected or deemed to be useful [Leibowitz and Vining, 2003;Johnson et al, 2010].…”
Section: Small Wetlands As Biogeochemical Hotspots In Landscapesmentioning
confidence: 90%
“…Global datasets such as the HydroLAKES database which characterizes the area, volume, and residence times of lakes are truncated at waterbodies less than 10 ha in area [Messager et al, 2016] -thus would not be useful when attempting to quantify the truly smaller systems. The Des Moines Lobe landscape is part of the Prairie Pothole Region, which has numerous depressional features with surface areas ranging from 100 m 2 to 5x10 4 m 2 [Van Meter and Basu, 2015]. Analyses by Van Meter and showed that there is a power law relationship between the number of depressional wetlands in the lobe and their surface areas ( Figure 5; N = 2x10 10 x SA -1.67 ; p <0.001; r 2 = 0.99).…”
Section: Regression Relationships For Scalingmentioning
confidence: 98%
See 3 more Smart Citations